2024
DOI: 10.26599/fshw.2022.9250084
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment in combination with Bifidobacterium breve HNXY26M4 intervention amplifies neuroprotective benefits in a mouse model of Alzheimer's disease by modulating glutamine metabolism of the gut microbiome

Abstract: The gut microbiota-brain axis has emerged as a novel target for Alzheimer's disease (AD), a neurodegenerative disease characterised by behavioural and cognitive impairment. However, most previous microbiome-based intervention studies have focused on single factors and yielded only modest cognitive improvements. Here, we proposed a multidomain intervention strategy that combined Bifidobacterium breve treatment with environmental enrichment (EE) training. In this study, we found that compared with EE or B. breve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In addition, oral administration of Bifidobacterium lactis ameliorates cognitive dysfunction in Aβ-injected mice through attenuation of ERK and JNK phosphorylation [ 55 ]. As well as it has been reported that Lactobacillus species act as protective from environmental stressors [ 56 ], and Bifidobacterium breve alleviated Aβ-induced cognitive impairment and enhanced synaptic function in AD mice [ 57 ]. We previously demonstrated that orally supplemented B. breve MCC1274 mitigated AD pathologies, as indicated by improved memory impairment, reduced amyloidosis and neuroinflammation, and improved synaptic plasticity, in both young AD model and WT mice [ 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, oral administration of Bifidobacterium lactis ameliorates cognitive dysfunction in Aβ-injected mice through attenuation of ERK and JNK phosphorylation [ 55 ]. As well as it has been reported that Lactobacillus species act as protective from environmental stressors [ 56 ], and Bifidobacterium breve alleviated Aβ-induced cognitive impairment and enhanced synaptic function in AD mice [ 57 ]. We previously demonstrated that orally supplemented B. breve MCC1274 mitigated AD pathologies, as indicated by improved memory impairment, reduced amyloidosis and neuroinflammation, and improved synaptic plasticity, in both young AD model and WT mice [ 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%